The Production Forest area Surrounding Badaro Village, Modayag District, East Bolaang Mongondow Regency, and the Non-Timber forest Products that the Local Population Uses - Pasambuna, Hendratno; Nini, Wa; Pobela, Elva; Karundeng, Feldy; Paputungan, Nining G.; Tawaja, Ramzia Djangoan; Paputungan, Riski (Jurnal Biologi Tropis, 2025)
Forest products are used by the communities that surround forest regions to meet their basic requirements. Finding out what kinds of non-timber forest products the people in the Production Forest Area near Badaro Village, Modayag District, East Bolaang Mongondow Regency, use is the goal of this study. The survey method or direct observation combined with interview-based data gathering techniques is the methodology employed in this study. Non-timber forest products with economic value are used by the locals in the Modayag District of East Bolaang Mongondow Regency, which includes Badaro Village. The four categories of non-timber forest products are as follows: First, ornamental plant groups, which include ferns, fan palms, and vegetables. Fruit groups like Amok/Sukun come in second. Third are plant groupings like aromatic pandan rice leaves and animal groups like red jungle fowls. It is possible to get this conclusion from the discussion and results description. It is intended that the government, academics, environmental observers, and the community will all be able to raise awareness of the value of using sustainable forest products at all societal levels, particularly for those who live and rely on them.